Can a single-port robot be safely used for robotic total gastrectomy for advanced gastric cancer? First experience using the da Vinci SP platform. (7th June 2022) - Cui, Hao; Cui, Jian-Xin; Zhang, Ke-Cheng; Liang, Wen-Quan; Li, Shu-Yan; Huang, Jun; Chen, Lin; Wei, Bo
Abstract: Background: Many studies have shown the operative feasibility and safety of robotic gastrectomy. Surgeons are pursuing single-port (SP) surgery to leverage the advantages of minimally invasive gastrectomy. The purpose of this study was to describe technical considerations and short-term outcomes from the first reported SP robotic total gastrectomy (RTG) using the da Vinci SP platform. Methods: A 75-year-old patient with a body-mass index of 19.8 kg/m 2 and clinical stage III cancer (cT3N+M0) underwent SP RTG on 22 January 2022 at the Department of General Surgery, the Chinese PLA General Hospital. All procedures were performed successfully using the da Vinci SP robotic platform. Results: The SP RTG was successfully performed with D2 lymphadenectomy including No. 10 lymph-nodes dissection and extracorporeal Roux-en-Y anastomosis. Except for subcutaneous emphysema, no severe adverse events occurred during the operation. According to a visual analogue scale (VAS), the subjective feeling of post-operative pain was given a VAS score of 3 of 10 on Post-Operative Day 1 (POD 1), 1 of 10 on POD 3, and 1 of 10 on POD 7. We removed the gastric tube on POD 2 and advised sipping water, a liquid diet, and a soft diet on PODs 2, 4, and 6, respectively. The patient was discharged without any complications on POD 8. Conclusion: RTG is technically feasible and safe using the da Vinci SP robotic platform. To our knowledge, this is the first study using the da Vinci SP platform in RTG for advanced gastric cancer in elderly patients. To verify its superior operative outcomes, further clinical trials are needed.